2003
DOI: 10.1034/j.1398-9995.2003.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar levels of nitric oxide in exhaled air in non‐asthmatic rhinitis and asthma after bronchial allergen challenge

Abstract: The difference in eNO between non-asthmatic rhinitis and asthma at baseline is abolished after allergen exposure due to a significantly greater increase in eNO in non-asthmatic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
3
17
0
3
Order By: Relevance
“…These findings extend those of challenge test results from studies performed by other groups with Further analyses in the present subdivided groups of latexsensitised patients with regard to the location of the clinical response show no difference in eNO change between asthmatic and rhinitic groups. These results, confirming the respective findings of LOPUHAÄ et al [1], as well as the relationship of eNO changes with lung function in the present latex-sensitised subjects, correspond to the assumption that seemingly separate clinical disorders, namely allergic asthma and rhinitis, are manifestations of a unique entity with a common underlying pathophysiological process and only gradual differences in the involvement of the upper and lower airways [24][25][26]. The latter can be verified by stronger and, using categorical interpretation, more frequent methacholine hyperresponsiveness (77% of the asthmatic and 37% of the rhinitic responders in the present study were hyperresponsive) and allergen-induced sRaw increases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings extend those of challenge test results from studies performed by other groups with Further analyses in the present subdivided groups of latexsensitised patients with regard to the location of the clinical response show no difference in eNO change between asthmatic and rhinitic groups. These results, confirming the respective findings of LOPUHAÄ et al [1], as well as the relationship of eNO changes with lung function in the present latex-sensitised subjects, correspond to the assumption that seemingly separate clinical disorders, namely allergic asthma and rhinitis, are manifestations of a unique entity with a common underlying pathophysiological process and only gradual differences in the involvement of the upper and lower airways [24][25][26]. The latter can be verified by stronger and, using categorical interpretation, more frequent methacholine hyperresponsiveness (77% of the asthmatic and 37% of the rhinitic responders in the present study were hyperresponsive) and allergen-induced sRaw increases.…”
Section: Discussionsupporting
confidence: 83%
“…These findings suggest that cigarette smoke and corticosteroids initiate distinct molecular mechanisms influencing nitric oxide concentrations in the airways. KEYWORDS: Allergy, bronchial asthma, latex, nitric oxide E xhaled nitric oxide (eNO) has been described as a marker of allergic airway inflammation in both rhinitic and asthmatic subjects [1][2][3][4][5][6][7]. eNO levels may be elevated in patients before asthmatic symptoms develop [8,9].…”
mentioning
confidence: 99%
“…Thus, IgE-mediated allergy has been reported to be responsible for elevated FeNO. 27 We have shown that a significant increase of eNO during the pollen season in atopic rhinitis patients influences the impact of inflammation on the upper airways. Our results are consistent with earlier reports by Henriksen et al 28 They found that an increase in eNO on allergen exposure, particularly in hyperresponsive subjects, may be suggestive of airway inflammation and an increased risk for developing asthma in AR.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2,(4)(5)(6) Moreover, FeNO is known to be elevated in bronchial allergen challenges (BAC), increasing a few hours after the allergen is inhaled. (7)(8)(9)(10) However, the dynamics of post-BAC FeNO changes are still not understood, especially in terms of peak values and the duration of the effect. Furthermore, little is known about any possible associations between FeNO and forced expiratory volume in 1 sec(FEV 1 ), which is measured routinely as an outcome of BAC, or between FeNO and nonspecific bronchial hyperreactivity (BHR).…”
Section: Introductionmentioning
confidence: 99%